MAQĀṢID ASY-SYARĪ‘AH PENGERTIAN DAN PENERAPAN DALAM EKONOMI ISLAM - AMINAH AMINAH (IAIN Padangsidimpuan, 2017)
Basically syariah includes a broadly discussion, because besides talking about the interaction with Allah (ibadah), it is also with another human (muamalah). The focus of muamalah is to manage the Muslims life in their interaction with others, include the vital thing, economic side. Economic issues closely related to the benefits; because it is very important in Islamic economy and occupy a very central issues to judge. The growing era developed with every different innovations of life, appearing new events untapped by classical fiqh. On the other side, with the varieties of benefits come, we must be careful with the benefits that will be reached